Morphological and Pathogenic Characterization of Genetically Diverse Sclerotinia Isolates from European Red Clover Crops (Trifolium Pratense L.). Issue 4 (6th December 2012) - Vleugels, Tim; Baert, Joost; van Bockstaele, Erik
Abstract Clover rot, an important disease in European red clover crops, is caused by Sclerotinia trifoliorum or Sclerotinia sclerotiorum. Until today, little is known about the variation in aggressiveness among Sclerotinia isolates from red clover. Aggressiveness has never been correlated with morphological characteristics. Rapidly growing isolates may be more aggressive, but this was never investigated in S. trifoliorum before. Also nothing is known about the link between sclerotia production and aggressiveness. Oxalic acid is an important pathogenicity factor in Sclerotinia species, but its effect on aggressiveness is unknown in S. trifoliorum isolates. For this study, we selected 30 Sclerotinia isolates from 25 locations Europe: 26 S. trifoliorum isolates and 4 S. sclerotiorum isolates from two locations in France (Fr.A and Fr.B). For each isolate, the in vitro growth speed, sclerotia production, oxalate production and aggressiveness were analysed and correlations were estimated between aggressiveness and the other characteristics. Aggressiveness was assessed in vitro on detached leaves and in a greenhouse on young plants. Our isolates differed significantly in growth speed, sclerotia production, oxalate production and aggressiveness. The infections on detached leaves and young plants revealed interaction between isolates and plant genotypes and between isolates and cultivars, but there was no indication that pathotypes exist. In vitro growth speed and in vitro aggressiveness on detached leaves were positively correlated with aggressiveness on young plants, while sclerotia production was negatively correlated with aggressiveness on young plants. These factors can be used as predictors of aggressiveness of Sclerotinia isolates from red clover crops.